2020
DOI: 10.3390/en13205383
|View full text |Cite
|
Sign up to set email alerts
|

Biomass to Syngas: Modified Stoichiometric Thermodynamic Models for Downdraft Biomass Gasification

Abstract: To help meet the global demand for energy and reduce the use of fossil fuels, alternatives such as the production of syngas from renewable biomass can be considered. This conversion of biomass to syngas is possible through a thermochemical gasification process. To design such gasification systems, model equations can be formulated and solved to predict the quantity and quality of the syngas produced with different operating conditions (temperature, the flow rate of an oxidizing agent, etc.) and with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Guo et al showed that the excessive amount of biomass and coal blends have advantages to the co-combustion process. They reported the optimum blending ratio of 30% for the composite biomass pellets (CBPs) and coal blends [18].…”
Section: Comparison Of Emission Concentrations From Different Biomass Blending Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al showed that the excessive amount of biomass and coal blends have advantages to the co-combustion process. They reported the optimum blending ratio of 30% for the composite biomass pellets (CBPs) and coal blends [18].…”
Section: Comparison Of Emission Concentrations From Different Biomass Blending Ratiosmentioning
confidence: 99%
“…The European Union has fixed a mandatory target of getting 20% share of renewable resources in the energy mix by 2020 [16]. Among various available renewable resources, such as solar, hydro, and geothermal; biomass presents a viable substitute owing to its availability and capability of meeting diverse energy needs, including electricity generation, vehicle fueling, and domestic heating [17,18]. Biomass is considered to be the fourth largest fuel after coal, oil, and natural gas, and compared to fossil fuels, biomass is termed as carbon-neutral [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to prevent an excessive amount of these contaminants from reaching the engine to maintain the operation and endurance of components such as valves, combustion chamber, and pistons [36]. Tar yield depends on the gasifier type [37] and the downdraft reactors produce syngas with a low tar content [38,39] and, therefore, was chosen to implement this very simple filtration stage. The fuel tank was removed from the generator for safety reasons.…”
Section: Portable Petrol Generator and Femto Gasifiermentioning
confidence: 99%
“…Tauqir et al [10] modelled the gasification process through equilibrium approach, using ASPEN Plus software and studied the effect of Tgasification, MC and ϕ on the SC, lower heating value of the syngas (LHVsyngas) along with hot gas efficiency and cold gas efficiency (ηcoldgas). For wood and agricultural based biomasses, Ayub et al [11] improved the equilibrium model 115-2 by adding correction factors based on the experimental data into the design equations. Caglar et al [12] calculated the variation of the production of syngas yield, hydrogen production, methane production, carbon dioxide emission and gasification efficiencies with respect to Tgasification and different gasifying agents.…”
Section: Introductionmentioning
confidence: 99%